Characterizing sleep in adults with Type 1 and Type 2 diabetes - Lydi-Anne Vézina-Im; Stéphane Turcotte; Anne-Frédérique Turcotte; Dominique Beaulieu; François Boudreau; Christine Morin (Sleep Epidemiology)
Objective: To characterize sleep/insomnia and sleep habits among adults with type 1 (T1D) and type 2 (T2D) diabetes. Methods: Adults with T1D or T2D were invited to complete an anonymous cross-sectional online survey containing validated self-reported measures on sleep quality, sleep health, insomnia severity, and questions on sleep habits. Multivariate linear and logistic regression analyses were performed. Results: A total of 303 adults (20–86 years; 75.3 % female) with T1D (n = 121) and T2D (n = 182) completed the whole survey. Sleep quality was associated with type of diabetes (β=1.27; 95 % CI: 0.28, 2.27) and income (β=-1.18; 95 % CI: -2.11, -0.26) when adjusted for sex and age. Adults with T2D and with a lower income reported poorer sleep quality. Sleep timing variability (rs=0.25–0.33; p < 0.05) and caffeine consumption before bedtime (rs=0.14–0.17; p < 0.05) were the sleep habits that were correlated with sleep quality, sleep health, and insomnia severity when adjusted for sex, age, and income. Sleep timing variability ≥3 times/week was associated with age (OR=0.97; 95 % CI: 0.94, 0.99). Caffeine consumption before bedtime ≥3 times/week was associated with sex × age (p = 0.0165). Younger males were the most likely to indicate adopting this sleep habit. Conclusions: Adults with T2D and those reporting a lower income seem at high risk for poor sleep quality. Adults with diabetes mentioning sleep issues, especially those with T2D and with a lower income, should have access to inexpensive behavioral sleep interventions. Younger adults with diabetes should receive counseling promoting healthy sleep habits, especially males in the case of caffeine consumption before bedtime.